Carnosic Acid Suppresses the Development of Oral Squamous Cell Carcinoma via Mitochondrial-Mediated Apoptosis - Min, Fenghe; Liu, Xin; Li, Yuan; Dong, Mingyuan; Qu, Yidi; Liu, Weiwei (Frontiers in Oncology, 2021)
Oral squamous cell carcinoma (OSCC) predominantly consists of squamous cells and is the tumor with the highest incidence of the head and neck. Carnosic acid (CA), a natural monomer drug obtained from rosemary and salvia, shows various pharmacological effects, including of tumor development. This study aimed to assess for an effect of CA on the development of OSCC and the underlying mechanisms. In CAL27 and SCC9 cells, CA inhibited cell proliferation and migration, increased intracellular levels of reactive oxygen species (ROS) and Ca2+, decreased the mitochondrial membrane potential (MMP), and promoted apoptosis. In CAL27- and SCC9-xenotransplanted BALB/c nude mice, CA inhibited the tumor growth without affecting the body weight and tissue morphology. CA upregulated Bax, Bad, cleaved Caspase-3 and -9 levels, and the cleaved PARP1/PARP1 ratio but downregulated Bcl-2 in CA-treated OSCC cells and OSCC cells-xenotransplanted BALB/c nude mice. These results indicate that CA suppresses OSCC at least via the mitochondrial apoptotic pathway and offers this natural compound as a potential therapeutic against OSCC.